Feeding mechanisms in two treefrogs, Hyla nana and Scinax nasicus (Anura: Hylidae). - Vera Candioti, María Florencia (2004)
After the description of the chondrocranium, hyobranchial apparatus, associated musculature, buccal apparatus, buccopharyngeal cavity, digestive tract, and gut contents, it was possible to define the feeding modes of Scinax nasicus and Hyla nana tadpoles (Gosner Stages 31–36). Scinax nasicus larvae are “typical” microphagous tadpoles, with keratodonts and robust rostrodonts appropriate for rasping surfaces and mincing of food particles; the buccopharyngeal cavity is equipped with filtering structures and has a conspicuous glandular zone and a highly developed branchial basket. In contrast, H. nana tadpoles have a modified buccal apparatus; the reduction of the buccopharyngeal and branchial basket structures, together with the high lever–arm ratio and the great development of the depressor muscles of the buccal floor are indicative of macrophagous feeding.